Implementation of Regional Regulation Number 7 of 2017 Concerning Public Order, Especially Social Order by the Civil Service Unit of the City of Tomohon - Kalengkongan, Edwin; Bogar, Wilson; Mandagi, Marthinus (Technium Social Sciences Journal, 2021)
This study aims to describe, analyze, and interpret the implementation of local regulation no. 7 of 2017 concerning public order, especially social order by the Tomohon Civil Service Police Unit [1]. The results showed that: a) lack of understanding of the community regarding what are the benefits, goals and objectives of local regulations regarding social order, the community does not know because of the lack of socialization carried out by the implementor, so far the socialization has been carried out only in oral form, b) that the process of taking preventive measures has been carried out in the form of conducting patrols by the Tomohon Civil Service Police Unit with a schedule of 1 x 24 hours for 2 patrol groups and, c) Whereas the enforcement process is based on the element of what mistakes he has committed. If it is related to population problems to be resolved or processed, whether it is a Certificate of Domicile (SKD) or the issuance of an Identity Card (KTP). For matters of immorality and alcoholic drinks, an investigation is made in the form of an Investigation Report (BAP) and then issues a Statement Letter as a form of guidance, d) That legal enforcement is not following the mandate of Perda No. 7 of 2017 concerning Public Order because there are no cases that have been continued until the trial of minor criminal acts.